Chrysanthemums and thorns the untold story of modern Japan - Reingold, Edwin M. (St. Martin's Press, 1992)
A comprehensive, highly original look at modern Japan, including business practices, education, attitudes toward sex, issues of class, military power, and Japan's role in world affairs.